The Impact of Corruption on Entry Strategy: Evidence from Telecommunication Projects in Emerging Economies - Uhlenbruck, Klaus; Rodriguez, Peter; Doh, Jonathan; Eden, Lorraine (Organization Science, 2006)
With globalization and the growth in emerging economies, multinational enterprises (MNEs) now frequently confront challenges associated with corrupt governments. Already, a growing body of research has demonstrated that corruption significantly reduces a country’s aggregate inflows of foreign direct investment through its effects on firm performance. We move the analysis of corruption from aggregate financial flows toward managerial theory and practice by examining how firms adjust their strategy for entering foreign markets in corrupt environments and how different types of corruption affect firms’ choices. Building on institutional theory, we predict that MNEs will respond to pervasive and arbitrary corruption in a host country by selecting particular types of equity and nonequity modes of entry. Using data on 220 telecommunications development projects in 64 emerging economies, we find that firms adapt to the pressures of corruption via short-term contracting and entry into joint ventures. We also find that the arbitrariness surrounding corrupt transactions has a significant impact on firms’ decisions, in addition to the overall level of corruption. In contrast to extant research, we show that MNEs use nonequity-entry modes or partnering as an adaptive strategy to participate in markets despite the presence of corruption.